Mitochondrial Protein Akap1 Deletion Exacerbates Endoplasmic Reticulum Stress in Mice Exposed to Hyperoxia - Sidramagowda Patil, Sahebgowda; Soundararajan, Ramani; Fukumoto, Jutaro; Breitzig, Mason; Hernández-Cuervo, Helena; Alleyn, Matthew; Lin, Muling; Narala, Venkata Ramireddy; Lockey, Richard; Kolliputi, Narasaiah; Galam, Lakshmi (Frontiers in Pharmacology, 2022)
Subjects with acute lung injury (ALI) and its severe form, acute respiratory distress syndrome (ARDS), are treated with high concentrations of supplemental oxygen. However, prolonged exposure to high concentrations of oxygen increases the levels of reactive oxygen species (ROS) and causes mitochondrial damage and accumulation of mis-folded proteins in the endoplasmic reticulum (ER). Akap1 (A-kinase anchoring protein 1), a mitochondrial protein, plays an important role in mitochondrial homeostasis. Akap1 deletion causes cardiac injury, impaired neuron development, and mitochondrial dysfunction. Wild type and Akap1-/- mice were exposed to hyperoxia for 48 h to investigate the function of Akap1 deletion in lung injury. Akap1 deletion enhances the severity of hyperoxia-induced ALI in mice. This study indicates that Akap1-/- mice exposed to hyperoxia undergo ER stress which is associated with an increased expession of BiP, JNK phosphorylation, eIF2α phosphorylation, ER stress-induced cell death, and autophagy. This suggests that Akap1 deletion causes ER stress in mice and that hyperoxia exposure cause’s activation of ER stress associated complications.